2021
DOI: 10.2217/cer-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

Micronized purified flavonoid fraction in the treatment of hemorrhoidal disease

Abstract: Hemorrhoidal disease (HD) is common in adults. Treatment is largely conservative, although more invasive procedures may be required. Venoactive drugs such as micronized purified flavonoid fraction (MPFF) are widely used, but a recent and comprehensive review of supporting evidence is lacking. In acute HD, MPFF can reduce HD symptoms such as bleeding, pain, anal discomfort, anal discharge and pruritus. In patients undergoing surgery, postoperative adjunct MPFF consistently reduces pain, bleeding duration and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
0
7
0
4
Order By: Relevance
“…19,31 Peran Micronized Purified Flavonoid Fraction (MPFF) Micronized Purified Flavonoid Fraction atau MPFF adalah salah satu obat phlebotonik oral yang sebagian besar mengandung micronized diosmin (90%) dan campuran beberapa flavonoid lain yaitu diosmetin, hesperidin, linarin, dan isorhoifolin (10%). 29,31,32 MPFF juga merupakan agen flavonoid phlebotonik yang telah dimikronisasi hingga partikelnya memiliki ukuran yang lebih kecil dari 2 μm. Mikronisasi pada MPFF ini tidak hanya meningkatkan daya absorpsi usus dan solubilitas namun juga mengurangi durasi untuk beraksi pada tubuh.…”
Section: Penatalaksanaan Hemoroidunclassified
See 1 more Smart Citation
“…19,31 Peran Micronized Purified Flavonoid Fraction (MPFF) Micronized Purified Flavonoid Fraction atau MPFF adalah salah satu obat phlebotonik oral yang sebagian besar mengandung micronized diosmin (90%) dan campuran beberapa flavonoid lain yaitu diosmetin, hesperidin, linarin, dan isorhoifolin (10%). 29,31,32 MPFF juga merupakan agen flavonoid phlebotonik yang telah dimikronisasi hingga partikelnya memiliki ukuran yang lebih kecil dari 2 μm. Mikronisasi pada MPFF ini tidak hanya meningkatkan daya absorpsi usus dan solubilitas namun juga mengurangi durasi untuk beraksi pada tubuh.…”
Section: Penatalaksanaan Hemoroidunclassified
“…Mikronisasi pada MPFF ini tidak hanya meningkatkan daya absorpsi usus dan solubilitas namun juga mengurangi durasi untuk beraksi pada tubuh. 19,32 Dalam penatalaksanaan hemoroid, MPFF dipakai untuk melancarkan tonus pembuluh darah vena (venous tone), menghambat pelepasan prostaglandin, dan mengurangi gejalagejala akut yang berkaitan dengan hemoroid kelas I dan II. 32,33 Beberapa penelitian menunjukkan bahwa MPFF dapat meningkatkan resistensi kapiler dan menurunkan permeabilitas kapiler dengan menghambat aktivasi, migrasi, dan adhesi leukosit.…”
Section: Penatalaksanaan Hemoroidunclassified
“…Hemorrhoidal disease (HD) is a frequently reported anorectal condition, characterized by distal displacement of the hemorrhoidal cushions and by symptomatic dilation of the anal venous plexus often reported following a persistent high pressure within the hemorrhoidal plexus and which can occur for various reasons ( Lohsiriwat, 2012 ; Godeberge et al, 2021 ). Overall, several main mechanisms are involved in the pathophysiology of HD, including mechanical injury to the anal cushions, abnormal venous dilatation, venous stasis, vascular thrombosis, tissue inflammation, and degenerative process in the collagen fiber deposition ( Lohsiriwat, 2012 ; Godeberge et al, 2021 ). Most symptoms result from the enlargement of internal hemorrhoids and are generally associated with constipation, diarrhea, or prolonged defecation, but also with pregnancy and childbirth ( Beck et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…The specific mechanism of action of phlebotonic agents, above all if of natural origin, has not been well established; however, their use is associated with the strengthening of blood vessel walls, increase of venous tone, and increase in lymphatic drainage and normalization of capillary permeability ( Quijano and Abalos, 2005 ; Beck, 2011 ; Lohsiriwat, 2012 ; Perera et al, 2012 ; Martinez-Zapata et al, 2016 ). Furtherly, they showed antioxidant and anti-inflammatory effects, which contribute to vasoprotective actions ( Lohsiriwat, 2012 ; Godeberge et al, 2021 ). In addition, recent evidence has shown that flavonoids but also vitamin C are involved in the modulation of the anti-senescence gene Sirtuin 1 and with the regulation of nitric acid and that its suppression is associated with cellular mitosis and apoptosis ( hajevand-Khazaei et al, 2018 ; Wei et al, 2014 ; Shokri Afra et al, 2019 ; Iside et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation